Teaching and learning chemical transformation: a comparison of curriculum texts and teaching resources in the French-speaking part of Switzerland and in France - Sudriès, Marie; Ligozat, Florence; Cross, David (Swiss Journal of Educational Research, 2023)
The aim of this study is to investigate the conditions under which the chemical transformation concept is taught and learned at lower secondary school (13- to 15-year-old students) in the French-speaking part of Switzerland and France. Chemical transformation is a central concept of the chemistry curriculum, and it can be a key to understand natural/technical phenomenon like the carbon cycle, meaning this concept can support the understanding of global warming. The analysis of curriculum texts and teaching resources shows that for these reasons, chemical transformation is also part of biology/geography/geology curriculums. The purpose of this work is to understand how this concept can be a tool for students to understand complex issues and can contribute to environmental science literacy.